Petrogenesis of Proterozoic lamproites and kimberlites from the Cuddapah Basin and Dharwar Craton, southern India - Rao, N; Gibson, SA; Pyle, D; Dickin, A (2004)
Proterozoic mafic potassic and ultrapotassic igneous rocks implaced at the Cuddapah Basin and Dharwar Craton of the southern Indian shield are among the earliest recorded on Earth. Lamproiles intrude the basin and its NE margin, whereas kimberlites intrude the craton to the west of the basin. Kimberlites occur in two spatially separate groups: the non-diamondiferous Mahbubnagar cluster that was emplaced at 1400 Ma and is of a similar age to the Cuddapah lamproites, and the predominantly diamondiferous Anantapur cluster, emplaced at ∼1100 Ma. Despite their Proterozoic ages, some of the kimberlites are petrographically fresh. Distinct variations are evident in the major and trace element concentrations ofthe diamondiferous and non-diamondiferous kimberlites. The latter have higher concentrations of Fe, Ti, Zr, Hf and Sc, and lower Ni contents and La/Sm ratios. All of the kimberlites have high La/Yb ratios (65-180) and positive εNdi values (0.5-4.5), which suggests that their source regions were metasomatized by small-fraction melts derived from the depleted upper mantle, shortly prior to kimberlite genesis. Cuddapah Basin lamproites have similar La/Yb ratios but much lower εNdi values (-6 to -7) and appear to have been derived from ancient metasomatized sub-continental lithospheric mantle. The Proterozoic ambient mantle is believed to have had a higher potential temperature than at the present day such that small amounts of lithospheric extension may account for the genesis of the kimberlites and lamproites of southern India without the need for a mantle plume. © Oxford University Press 2004; all rights reserved.